2010
DOI: 10.3109/00048671003631159
|View full text |Cite
|
Sign up to set email alerts
|

Do Antisocial Females Exhibit Poor Outcomes in Adulthood? An Australian Cohort Study

Abstract: Both males and females exhibiting AO and LCP antisocial behaviour are at increased risk of serious adverse outcomes in young adulthood. The significant loss to follow up of high-risk groups suggests the important relationship between early antisocial behaviour and problems in adulthood have been underestimated. Further research is required to understand antisocial behaviour in adolescence, identify factors that reinforce its continuity into adulthood, and identify interventions which are able to modify adult o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 47 publications
8
52
1
Order By: Relevance
“…The most common current offense for respondents (for which they were serving a sentence or awaiting disposition) was drug-related (32 %), and many respondents reported criminal records and past experience with the criminal justice system (e.g., arrests, jail, and/or prison terms). 10 All-in-all, these women are fairly typical of incarcerated women in the USA and Canada. 8 Those serving weekend or "shock" incarceration sentences were excluded from the sampling frame.…”
Section: Sample Methods and Analytic Approach Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The most common current offense for respondents (for which they were serving a sentence or awaiting disposition) was drug-related (32 %), and many respondents reported criminal records and past experience with the criminal justice system (e.g., arrests, jail, and/or prison terms). 10 All-in-all, these women are fairly typical of incarcerated women in the USA and Canada. 8 Those serving weekend or "shock" incarceration sentences were excluded from the sampling frame.…”
Section: Sample Methods and Analytic Approach Samplementioning
confidence: 99%
“…Due to the potential for important contextual differences, our analyses include dummy codes for the specific data collection sites. 10 Sixty-percent had been convicted of a felony prior to their current incarceration, 59 % had served at least one jail term as an adult, and 98 % had been arrested at least one before.…”
Section: Sample Methods and Analytic Approach Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal studies, including the MUSP, the Dunedin cohorts and the Australian Temperament Study, have shown that antisocial behaviours persist into adulthood. Those who manifest these from childhood and adolescence exhibit higher levels of substance abuse, poorer adjustment in relationships (204) and elevated symptoms of anxiety and depression (205,206). Interestingly, antisocial behaviour has not however been shown to predict alcoholic bingeing (205), which is commonly associated with acts of violence; it is possible that other temporalities apply.…”
Section: Antisocial Behaviour Aggression and Violencementioning
confidence: 99%
“…Those who manifest these from childhood and adolescence exhibit higher levels of substance abuse, poorer adjustment in relationships (204) and elevated symptoms of anxiety and depression (205,206). Interestingly, antisocial behaviour has not however been shown to predict alcoholic bingeing (205), which is commonly associated with acts of violence; it is possible that other temporalities apply. In the following section, the associations between alcohol and violence and mental health and violence will first be considered separately, after which commonalities and any literature on comorbidity and violence will be discussed.…”
Section: Antisocial Behaviour Aggression and Violencementioning
confidence: 99%